Life cycle analysis of polylactic acids from different wet waste feedstocks. (20th December 2022) - Kim, Taemin; Bhatt, Arpit; Tao, Ling; Benavides, Pahola Thathiana
Abstract: Producing a valuable chemical product through diversion of wet wastes can simultaneously resolve the problems associated with increasing wastes and greenhouse gas emissions from conventional chemical production processes. In this work, we investigated the life-cycle greenhouse gas emissions, water, and fossil-fuel consumption for waste-derived polylactic acids (PLA) from three different waste feedstocks, namely wastewater sludge, food waste, and swine manure, using the Greenhouse Gases, Regulated Emissions, and Energy Use in Technologies (GREET) model. The decarbonization potential of replacing fossil-based resins with the waste-derived polymer was also investigated. The results show that swine manure-to-PLA pathway was the least carbon intensive (−1.4 kgCO2 e/kg) among the three waste-to-PLA pathways on a cradle-to-grave basis, followed by the food waste case (−1.3 kgCO2 e/kg) and then by the wastewater sludge case (0.6 kgCO2 e/kg). In the baseline scenario, all three waste-to-PLA pathways were less carbon intensive than both fossil-based PET and HDPE on a cradle-to-grave basis: 66% (vs. PET) and 56% (vs. HDPE), 171 and 192%, 181 and 205% reduction in GHG emissions for wastewater sludge-, food waste-, and swine manure-to-PLA pathway, respectively. For all sensitivity cases investigated, the food waste- and swine manure-to-PLA pathways were significantly less carbon intensive than their fossil-counterparts. In terms of the annual decarbonization potential of replacing fossil-based PET or HDPE, the wastewater sludge- and food waste-pathway showed higher mitigation potential than the swine manure-pathway: i) 18–28 kilotons CO2 e-reduction per year for wastewater sludge pathway; ii) 23–26 kTCO2 e-reduction/yr for food waste pathway; and iii) about 5 kTCO2 e-reduction/yr for swine manure pathway depending on the type of conventional resin replaced. However, given the abundant availability of the swine manure feedstocks across the United States, the decarbonization potential of swine manure-based pathway can also increase as the plant capacity or the number of plants grow. Graphical abstract: Image 1 Highlights: Life cycle environmental impacts of waste-to-PLA production from wet wastes are investigated. Waste-derived PLAs are expected to emit up to 205% less GHGs than their conventional counterparts. Avoided business-as-usual scenario credits were the greatest mitigator to the PLAs GHG emissions. Use of renewable energy and lower PLA biodegradability can further decarbonize waste-to-PLA pathways. About 5–28 kTCO2 e/yr of GHG mitigation can be achieved by replacing PET or HDPE with the waste-PLA.